Functionality Extension for A D.C. Motor Speed Control Didactic System with PID Controller - Dale, Sanda; Costea, C.R.; Zsolt, S. (The scientific bulletin of Electrical Engineering Faculty, 2018)
The paper describes some functionality extensions for a D.C. motor speed control system with PID controller used as a didactic unit. The extensions are made in two directions: one at a physical-hardware level and the other one at software development of numerical algorithms and graphical interface. Both developments have the aim to extend and to get a more flexible paradigm for the control algorithms study on both continuous and discrete approach and to add the possibility to compare different control solutions.